2004
DOI: 10.2165/00019053-200422090-00003
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Effectiveness Analysis of Docetaxel in the Second-Line Treatment of Non-Small Cell Lung Cancer

Abstract: This model suggests, with its underlying assumptions and data, docetaxel 75 mg/m(2) in 3-weekly cycles is a cost-effective second-line treatment, from the perspective of the NHS, for pretreated NSCLC in terms of survival gains made for a reasonable increase in costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 6 publications
0
41
0
1
Order By: Relevance
“…Few economic studies of second-line treatments for advanced NSCLC have been published [21,27,28], and most are based on models using clinical trial data. The ICER of second-line erlotinib versus placebo in patients with previously treated advancedstage NSCLC has recently been published [29].…”
Section: Discussionmentioning
confidence: 99%
“…Few economic studies of second-line treatments for advanced NSCLC have been published [21,27,28], and most are based on models using clinical trial data. The ICER of second-line erlotinib versus placebo in patients with previously treated advancedstage NSCLC has recently been published [29].…”
Section: Discussionmentioning
confidence: 99%
“…These papers were published between 2002 and 2013; seven papers 63,65,66,[68][69][70][71] were published from 2010 onwards. All of the papers described full EEs using cost minimisation analysis (n = 1 64 ), cost-effectiveness analysis (n = 6 65,67,69,70,72 ) and/or cost-utility analysis (n = 6 [63][64][65]68,71,73 ) techniques. All but one study 70 used cost per QALY gained or cost per LY gained as the measure of cost-effectiveness.…”
Section: Cost-effectiveness Review: Resultsmentioning
confidence: 99%
“…All but one study 70 used cost per QALY gained or cost per LY gained as the measure of cost-effectiveness. The results of six studies 64,65,67,68,71,73 were derived from use of an economic model: one study 63 conducted an economic analysis alongside a RCT and the remaining four studies 66,69,70,72 conducted retrospective reviews of costs and/or benefits. Four studies 66,69,70,72 were carried out from a Canadian NHS perspective, two 67,71 from that of the UK NHS perspective, one 73 from the US perspective, three [63][64][65] from a European perspective and one 68 from a Thai payer perspective.…”
Section: Cost-effectiveness Review: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 The base case cost-effectiveness analysis reported a cost per life-year gained of 13,863 pounds sterling for docetaxel 75 mg/m 2 . Sensitivity analysis showed that the number of treatment cycles per patient, which affects total treatment cost, had the most influence on cost per life-year gained in the base case scenario.…”
Section: Discussionmentioning
confidence: 99%